PROSPECTIVE TEACHERS‘ ONLINE ASSESSMENT LITERACY IN SECOND-SEMESTER STUDENTS OF THE ENGLISH LANGUAGE EDUCATION STUDY PROGRAM AT UNDIKSHA - Noviyanti, Ni Komang Diah; Paramartha, A.A. Gede Yudha; Sulistia Dewi, Ni Luh Putu Eka (Universitas Suryakancana, 2025)
The rapid advancement of technology has transformed the educational landscape, making online assessment literacy an essential competency for prospective teachers. This study investigates the level of online assessment literacy among second-semester students in the English Language Education study program at Ganesha University of Education (Undiksha). Despite the absence of formal coursework on assessment at this stage, these students possess foundational knowledge from courses such as Wawasan Kependidikan (Educational Insights) and Perkembangan Peserta Didik (Student Development). A descriptive quantitative approach was employed, involving 121 students who completed a validated questionnaire comprising 28 items designed to measure their competencies across seven dimensions: Choosing (CH), Developing (DE), Administering (AD), Using-Decision (UD), Using-Grading (UG), Communication (CO), and Recognizing Ethics (RE). The findings reveal that the overall online assessment literacy of the participants falls within the “moderate” category, with notable variations across the dimensions. Female students performed better in Administering (AD) and Recognizing Ethics (RE), while male students excelled in Communication (CO) and Developing (DE). These results underscore the need for targeted strategies in subsequent semesters to address specific gaps and enhance overall competency. This study contributes to the literature by addressing research gaps on early-stage pre-service teachers’ online assessment literacy and offers actionable recommendations for curriculum development in teacher education programs.